2022
DOI: 10.3390/ijerph192214917
|View full text |Cite
|
Sign up to set email alerts
|

Bone Concentration of Ampicillin/Sulbactam: A Pilot Study in Patients with Osteonecrosis of the Jaw

Abstract: Osteonecrosis of the jaw (ONJ) occurs typically after irradiation of the head and neck area or after the intake of antiresorptive agents. Both interventions can lead to compromised bone perfusion and can ultimately result in infection and necrosis. Treatment usually consists of surgical necrosectomy and prolonged antibiotic therapy, usually through beta-lactams such as ampicillin/sulbactam. The poor blood supply in particular raises the question as to whether this form of antibiosis can achieve sufficient conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…We know from recent bioavailability studies that intraosseous concentrations of ampicillin/sulbactam in ORN are sufficient to treat Streptococcal and Staphylococcal species with intravenous therapy. 20 Our cohort did not reveal clindamycin resistance to GPC. A previous study demonstrated this resistance in mandibular infections.…”
Section: Discussionmentioning
confidence: 53%
“…We know from recent bioavailability studies that intraosseous concentrations of ampicillin/sulbactam in ORN are sufficient to treat Streptococcal and Staphylococcal species with intravenous therapy. 20 Our cohort did not reveal clindamycin resistance to GPC. A previous study demonstrated this resistance in mandibular infections.…”
Section: Discussionmentioning
confidence: 53%
“…The effect of antibiotic therapy on necrotic bone is largely unclear. Only a few studies have looked at the actual concentration of antibiotics in necrotic bone [24,25]. These studies describe low but sufficient concentrations of beta-lactam antibiotics to eradicate most bacteria, such as Streptococci and Staphylococci, which are typically present in ORN.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the systemic administration of ampicillin/sulbactam and clindamycin for MRONJ demonstrate their effectiveness in reaching therapeutic jawbone concentrations [23,62]. Ampicillin/sulbactam showed that a reduced duration of oral administration could be sufficient for MRONJ prevention [23], while clindamycin achieved sufficient concentrations in both vital and necrotic bone samples to combat common bacteria associated with MRONJ [62]. These findings underscore the viability of tailored antibiotic therapy as a comprehensive strategy for the prevention and treatment of MRONJ.…”
Section: Treatmentmentioning
confidence: 94%
“…This indicates that reduced oral antibiotic administration duration can be sufficient for MRONJ prevention when combined with proper preventive measures [61]. Studies on the systemic administration of ampicillin/sulbactam and clindamycin for MRONJ demonstrate their effectiveness in reaching therapeutic jawbone concentrations [23,62]. Ampicillin/sulbactam showed that a reduced duration of oral administration could be sufficient for MRONJ prevention [23], while clindamycin achieved sufficient concentrations in both vital and necrotic bone samples to combat common bacteria associated with MRONJ [62].…”
Section: Treatmentmentioning
confidence: 99%